2022
DOI: 10.24018/ejbmr.2022.7.1.1252
|View full text |Cite
|
Sign up to set email alerts
|

Distressed Debt Management & Lessons Learnt Through Case Management: Banking Industry in Kenya

Abstract: Deteriorating and troubled assets must be subjected to enhanced risk oversight and monitoring to ensure that appropriate action is taken in a timely manner, allowing a high level of obligor turnaround success and reduced risk of loss for the Lender/Financial Institution/Bank. It’s important for a Bank to harmonize Distressed Debt Management approach, called the Watch List (WL) Framework, and details the requirements to ensure timely adherence to regulatory requirements. The impairment requirements of Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Brigham and Daves (2003) financial distress happened before the firm faced bankruptcy or failure when the firm could not make the payment schedule or when cash flow estimates indicated that the firm would soon be unable to satisfy its obligations. Negative cash flow statements, falling margins and profits, revenue decreases, management stress, and employee turnover are all warning indications that a firm is in financial trouble (Muhammad, Mastuki, Darus, & Ghani, 2019;Muriithi, 2022;Munisamy et al, 2022;Arifin et al, 2022;Oner & Oner, 2022). Newton (1975) claimed that before declaring bankruptcy, an organisation would go through four stages of deterioration: incubation, cash scarcity, financial insolvency, and final insolvency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Brigham and Daves (2003) financial distress happened before the firm faced bankruptcy or failure when the firm could not make the payment schedule or when cash flow estimates indicated that the firm would soon be unable to satisfy its obligations. Negative cash flow statements, falling margins and profits, revenue decreases, management stress, and employee turnover are all warning indications that a firm is in financial trouble (Muhammad, Mastuki, Darus, & Ghani, 2019;Muriithi, 2022;Munisamy et al, 2022;Arifin et al, 2022;Oner & Oner, 2022). Newton (1975) claimed that before declaring bankruptcy, an organisation would go through four stages of deterioration: incubation, cash scarcity, financial insolvency, and final insolvency.…”
Section: Literature Reviewmentioning
confidence: 99%